The Effect of Liquidity Leverage and Company Size on Earnings Quality with Profitability as a Moderation Variable - Safitri, Munisa Laila; Amin, Muhammad Nuryatno (Universitas KH. Abdul Chalim Mojokerto, 2024)
This research aims to determine the effect of leverage, liquidity, and company size on earnings quality with profitability as a moderating variable. This type of research is quantitative research using secondary data obtained from the Indonesia Stock Exchange (IDX) website and processed using SPSS 25. The population in this research is energy sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. The research sample was taken using a purposive sampling method and a sample of 27 companies was obtained which was observed for 4 years after deducting outlier data with extreme values, the total research data processed was 100 data. The data analysis technique used is multiple linear regression analysis. The results of this research show that: (1) Leverage does not affect Earnings Quality. (2) Liquidity does not affect Earnings Quality. (3) Company size has a negative and significant effect on Earnings Quality. (4) Profitability cannot moderate Leverage on Earnings Quality. (5) Profitability can strengthen the influence of liquidity on earnings quality. (6) Profitability can strengthen the influence of company size on profit quality.